Salidroside suppresses gastric cancer progression via miR-1343-3p-mediated repression of ACOT11 and disruption of fatty acid metabolism - Zhang, Zhendong; Cao, Mingyuan; Du, Yuxin; Wang, Pingyi; Hou, Xinrui; Wang, Xiaoping (Frontiers in Oncology, 2025)
ObjectiveSalidroside, a bioactive compound derived from Rhodiola, has been demonstrated to upregulate the tumor suppressor miR-1343-3p, leading to suppression of gastric cancer growth. However, the precise molecular mechanisms underlying salidroside-mediated regulation of lipid metabolism via miR-1343-3p and its downstream mRNA targets remain poorly understood.MethodsThe interaction between miR-1343-3p and ACOT11 was evaluated through Pearson correlation analysis, sequence-based binding site alignment, and RNA immunoprecipitation (RIP) assays. The effects of salidroside treatment on cell proliferation, gene and protein expression, downstream metabolites, and energy production were assessed through a series of in vitro and in vivo experiments, including the CCK-8 assay, colony formation assay, RT-qPCR, Western blot, ELISA, cell transfection, and xenograft tumor models.ResultsThe expression of miR-1343-3p is negatively correlated with ACOT11 mRNA, which is closely associated with lipid metabolism. Salidroside significantly inhibits the proliferation of gastric cancer cells in a dose-dependent manner. Compared to untreated controls, salidroside-treated gastric cancer cells showed decreased ACOT11 mRNA/protein expression but increased miR-1343-3p levels. This was accompanied by elevated substrate fatty acyl-CoA concentrations with concurrent reductions in acetyl-CoA, FFA, and ATP. ACOT11 is a downstream target of miR-1343-3p, up-regulating miR-1343-3p expression reduces ACOT11 expression, while down-regulating miR-1343-3p expression increases ACOT11 expression. In vivo, salidroside significantly inhibited tumor growth in gastric cancer xenograft models.ConclusionsWe demonstrate that salidroside exerts anti-proliferative effects in gastric cancer by targeting the miR-1343-3p/ACOT11/FFA lipid metabolism signaling pathway, disrupting cancer cell energy production. These regulatory factors hold promise as novel therapeutic targets for gastric cancer.